Koliko knjig je mogoče prebrati v življenju? - Grdina, Igor (Knjižnica, 2011)
Purpose: the essay is mostly based on the analysis of primary sources (reminiscences) and addresses the question of which currents influenced the number of read books in various periods of modern history and particularly in the age of bourgeoisie in Slovenia. Methodology/approach: the researchwas carried out in accordance with the paradigms of new cultural history with special emphasis on the history of ideas and mentalities. Results: the mentality of enlightenment and national-awakening looked upon as highly non-elitist and emancipatory in Slovenia, led to efficient ways of spreading books and the circle of their readers. The publishers whose mass production became available to everyone, includingthe poorest strata of the society, ensured low prices of their book editions. Public and private libraries were an important instrument for the spread and creation of interest groups and national communities. Research limitation: the research is based on available resources; however, the lost or unknown resources could surely offer more answers. It is logical that some assumptions can be confirmed by a detailed analysis or by the review of manuscripts and other similar documents held in Slovenian libraries and abroad. Originality/practical implications: the analysisof reminiscences in the political, economical and historical context offers a new point of view of the social stand and cultural values of the Slovenian bourgeoisie in the early 20th century. The study presents the position of Slovenian people and identity shaped by the reading culture and language identity.
Keywords: cultural history; kulturna zgodovina; age of bourgeoisie; branje; reading; bralne navade; emancipacija; emancipation; knjižnice; libraries; Slovenia; Slovenija